BCAA insufficiency leads to premature ovarian insufficiency via ceramide‐induced elevation of ROS. Issue 4 (27th February 2023) - Guo, Xiao; Zhu, Yuemeng; Guo, Lu; Qi, Yiwen; Liu, Xiaocheng; Wang, Jinhui; Zhang, Jiangtao; Cui, Linlin; Shi, Yueyang; Wang, Qichu; Liu, Cenxi; Lu, Guangxing; et al.
Abstract: Premature ovarian insufficiency (POI) is a disease featured by early menopause before 40 years of age, accompanied by an elevation of follicle‐stimulating hormone. Though POI affects many aspects of women's health, its major causes remain unknown. Many clinical studies have shown that POI patients are generally underweight, indicating a potential correlation between POI and metabolic disorders. To understand the pathogenesis of POI, we performed metabolomics analysis on serum and identified branch‐chain amino acid (BCAA) insufficiency‐related metabolic disorders in two independent cohorts from two clinics. A low BCAA diet phenotypically reproduced the metabolic, endocrine, ovarian, and reproductive changes of POI in young C57BL/6J mice. A mechanism study revealed that the BCAA insufficiency‐induced POI is associated with abnormal activation of the ceramide‐reactive oxygen species (ROS) axis and consequent impairment of ovarian granulosa cell function. Significantly, the dietary supplement of BCAA prevented the development of ROS‐induced POI in female mice. The results of this pathogenic study will lead to the development of specific therapies for POI. Synopsis: Premature ovarian insufficiency (POI) is a disease featured by early menopause before 40 years. The current study identified that POI is related to metabolic disorders in these patients. Serum metabolomic analysis reveals a branch chain amino acid (BCAA) insufficiency‐related metabolic disorder in two independent cohorts of POI patients. BCAA insufficiency leads to POI via the upregulation of ceramide. Ceramide‐induced elevation of ROS contributes to the development of POI. BCAA supplement protects the ovaries from POI in mice. Abstract : Premature ovarian insufficiency (POI) is a disease featured by early menopause before 40 years. The current study identified that POI is related to metabolic disorders in these patients.